Autonomic Functioning in Young Adults Born at Extremely Low Birth Weight. (9th June 2015) - Mathewson, Karen J.; Van Lieshout, Ryan J.; Saigal, Saroj; Morrison, Katherine M.; Boyle, Michael H.; Schmidt, Louis A.
Autonomic functioning is altered in infants born at extremely low birth weight (ELBW; <1000 g), but we know little about how such alterations manifest in adulthood. We examined associations between birth weight and resting heart rate (R-R interval), high-frequency (HF) and low-frequency (LF) heart rate variability, and systolic (SBP) and diastolic (DBP) blood pressure, in 60 participants (ages 22-26) born at ELBW and free of major neurosensory impairment, and 79 controls born at normal birth weight (NBW; >2500 g). HF in the smallest-born ELBW participants was significantly lower than in NBW controls. In both groups, greater birth weight was associated with higher HF. Among ELBW survivors, lower birth weight predicted faster heart rate and higher DBP, but neither heart rate nor DBP appeared to be well-coordinated with baroreflex activity (LF), the principal mechanism for short-term blood pressure regulation. Adult autonomic regulation may be significantly altered in those born extremely preterm.